Exploring the typology of decision-makers, institutions, and incentives that shape health decisions in Pakistan and insulate decision makers from citizens feedback - Khan, Adnan A.; Khan, Romesa; Khawaja, Zainab; Ibrahim, Muhammad; Shaheen, Zarnab; Khan, Ayesha (Frontiers in Public Health, 2023)
Introduction In developing countries such as Pakistan, program and policies underperform in providing public good as weak institutions lead to decisions that are unresponsive to citizens and are driven by personal motivations of the incumbents. We describe the decision-making processes in the health sector through the framework of “Public Choice” theory which posits how individual motives shape institutional performance and direction. Methods We conducted 84 qualitative interviews with five types of stakeholders: politicians, senior and mid-level bureaucrats, donors, public health experts and media personnel spanning 2 periods over a decade. The initial interviews were conducted during 2013–2015 period and a case study on decision-making during the COVID-19 response was added in 2020–2022 period. Findings Most new ideas originate from top political leadership, guided by personal agendas or political expediency. Senior bureaucrats implement politicians’ agenda and mid-level officials maintain the status quo and follow established “authority.” Since officials’ performance, promotions, transfers, and the rare dismissals are based on tenure deviations rather than work performance, individuals and institutions are reluctant to take initiative without “consensus” among their colleagues often leading to inaction or delays that obviate initiative and reform. The public sector lacks institutional memory, formal information gathering, and citizen engagement, impacting public goods, health services, and policies. Media and donor personnel are important influencers. However, media mostly report only “hot issues” in health, with short publication and reader attention cycles. Donor personnel are the most likely to follow evidence for decision making, albeit while following their institutional priorities determined centrally. The COVID-19 response is presented as a contrast from usual practices, where evidence was used to guide decisions, as the pandemic was perceived as a national threat by the highest leadership. Conclusion Absence of citizen feedback and formal systems for evidence gathering and processing leads to decisions that neglect the needs of those they serve, prioritizing personal or political gains and perpetuating the status quo. However, the COVID-19 pandemic emphasized the importance of evidence-based decision-making and offers valuable lessons for reforming decision-making processes.